Digital humanities and christianity: an introduction - Hutchings, Tim; Clivaz, Claire (Introductions to digital humanities - religion, 2021)
Frontmatter -- Table of Contents -- Introduction -- Part I: Canon, corpus and manuscript -- The Bible in the digital age: multimodal Scriptures in communities -- Re-conceiving the Christian scholastic corpus with the scholastic commentaries and texts archive -- Canonical structure and the referencing of digital resources for the study of ancient and medieval Christianity -- Digitizing the ancient versions of the Apostolic Fathers: preliminary considerations -- Part II: Words and meanings -- Languages, texts, and inscribed objects of early Christianity: a survey of digital resources for students -- Between statistics and hermeneutics: the interplay between digital and traditional methods in Hebrew linguistics as evidenced from the study of hapax legomena -- Lexicography, the Louw–Nida Lexicon, and computational co-occurrence analysis -- Part III: Digital Christian history -- From inquisition to inquiry: inquisitorial records as a source for social network analysis -- Visualizing religious networks, movements, and communities: building Moravian Lives -- The theology of relational practice: digital modeling and the historical study of Christianity -- Liturgical history in a digital world: principles and future developments -- Part IV: Theology and pedagogy -- Digital pedagogy and spiritual formation: training for ministry and games for children -- Nested histories: digital humanities as pedagogical laboratory for early Christian studies -- Public theology behind the Great Firewall of China -- Index